Patent Licensing as the Implementation of Utilitarian Theory and a Part of Indonesia’s National Resilience - Kurniawan, Shelly; Tiopan, Demson (LEGAL BRIEF, 2024)
The rapid development of technology, whether stemming from research results or technological advancements, can be protected through intellectual property, specifically patents.  The regulation of patents is stipulated in Law Number 13 of 2016 concerning Patents, with amendments to several articles in Law Number 6 of 2023 concerning the Determination of Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation. Utilitarian theory, including its application in the context of patent licensing, is an integral part of patent regulation. However, the number of registered patent license agreements on the Directorate General of Intellectual Property's website is limited.  Yet, a proliferation of licenses can enhance a country's national resilience.  This study aims to investigate how the utilitarian theory within the patent system becomes a component of Indonesia's national resilience.  This normative legal study examined secondary literature and legal regulations related to patents, books, journals, and papers concerning intellectual property law, particularly patents.  The research findings indicate that the utilitarian theory can be implemented through licensing.  Registering patent licenses in agreements is a legal prerequisite for protection.  A high number of patent licenses can enhance Indonesia's resilience in terms of both economic and defense and security aspects